Relationship between Age and Parity with Late Onset Severe Preeclampsia at PKU Muhammadiyah Surabaya Hospital - Dwi Ariningtyas, Ninuk; Assidiqi Iman, Penta; Irfana, Laily; Anas, Muhammad (Universitas Muhammadiyah Surabaya, 2025)
Maternal and fetal mortality is 31.15% due to undetected preeclampsia leading to eclampsia. Pre-occurrence of eclampsia is often characterized by severe preeclampsia symptoms such as increased blood pressure, and proteinuria, furthermore, preeclampsia is also divided into 2 types, based on the time of symptom onset, in early-onset type preeclampsia appears at <34 weeks of gestation while for late-onset appears at >34 weeks of gestation. Extreme age and multigravida parity are risk factors for severe preeclampsia. This study aims to determine the relationship between age and parity with late-onset severe preeclampsia. This study used a cross-sectional study design, sampling method used nonprobability sampling techniques with observational analysis on pregnant women diagnosed with preeclampsia at PKU Muhammadiyah Surabaya Hospital for January 2022 - November 2023. The data collection instrument used medical record data, which was analyzed using Chi-Square. In the analysis obtained for the relationship between age and preeclampsia, the large p-value is 0.16 <0.05. The relationship of parity with preeclampsia is 0.004 < 0.05, thus proving a relationship between age and parity with late-onset severe preeclampsia at PKU Muhammadiyah Surabaya Hospital. In conclusion, there is a relationship between age and parity with late-onset severe preeclampsia at PKU Muhammadiyah Surabaya Hospital.